2018
DOI: 10.1097/aog.0000000000002620
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of von Willebrand Disease Screening in Girls and Adolescents With Heavy Menstrual Bleeding

Abstract: Despite recommendations by the American College of Obstetricians and Gynecologists for more than 15 years, fewer than 20% of postpubertal girls and adolescents with heavy menstrual bleeding underwent screening for von Willebrand disease in this cohort. Increased clinician awareness and adherence to recommended screening recommendations may increase diagnosis of von Willebrand disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…33,34 While blood loss of >80 mL is broadly used in clinical studies and trials to define heavy menstrual bleeding, this measurement (involving extracting hemoglobin from sanitary wear) is impractical outside of research settings; therefore, a requirement to change sanitary pads or tampons more often than hourly, clots at least 1 inch in diameter, or a low ferritin level are clinical predictors of heavy periods. 8 A PBAC score > 100 has also been shown to be a sensitive and specific indicator of blood loss exceeding 80 mL per cycle. 35…”
Section: Heavy Menstrual Bleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 While blood loss of >80 mL is broadly used in clinical studies and trials to define heavy menstrual bleeding, this measurement (involving extracting hemoglobin from sanitary wear) is impractical outside of research settings; therefore, a requirement to change sanitary pads or tampons more often than hourly, clots at least 1 inch in diameter, or a low ferritin level are clinical predictors of heavy periods. 8 A PBAC score > 100 has also been shown to be a sensitive and specific indicator of blood loss exceeding 80 mL per cycle. 35…”
Section: Heavy Menstrual Bleedingmentioning
confidence: 99%
“…5 Multidisciplinary adolescent hematology clinics have helped closed the gap between HMB onset and BD diagnosis, 6 but only 5% of women with HMB present to a hematologist 7 or get screened for common BDs. 8 At any age, a lack of patient and provider awareness causes a delay in diagnosis and bleeding complications during the reproductive lifespan of women with BD. 9 Standardization of HMB care across specialists lends the opportunity to improve diagnosis and treatment outcomes in adolescents with BD.…”
Section: Introductionmentioning
confidence: 99%
“…17 Improvements in the recognition and diagnosis of VWD in adolescent girls are also needed. 28 Despite evidence that VWD is among the most commonly encountered bleeding disorders in adolescents with abnormal uterine bleeding 29 and that testing may be cost-effective, 30 laboratory testing is performed infrequently 31,32 and diagnosis may be delayed into adulthood. 33 In 2001, the American College of Obstetricians and Gynecologists (ACOG) indicated that routine screening for coagulation disorders in adolescents with anovulatory bleeding was warranted, and that an underlying coagulopathy such as VWD should be considered in all patients (particularly adolescents) with abnormal uterine bleeding.…”
Section: Implications For Education and Researchmentioning
confidence: 99%
“…It also requires some additional considerations, most notably a detailed history of menstrual blood loss and control of acute menstrual hemorrhage, if present (Table ). Once the anemia is fully treated, it is important to consider evaluation for a bleeding disorder in patients with heavy menses prior to discharge from hematologic care . Dietary history must also be considered in adolescent females, as well as increased iron utilization or losses due to high levels of athletic activity (see “Runner's or athlete's anemia”) .…”
Section: Consultations To the Pediatric Hematology–oncology Specialistmentioning
confidence: 99%
“…Once the anemia is fully treated, it is important to consider evaluation for a bleeding disorder in patients with heavy menses prior to discharge from hematologic care. 22,40,41 Dietary history must also be considered in adolescent females, as well as increased iron utilization or losses due to high levels of athletic activity (see "Runner's or athlete's anemia"). 42 Oral iron therapy is the typical initial therapy, although for patients experiencing substantial fatigue, headaches, and/or exercise intolerance, intravenous iron may be considered to achieve a faster response.…”
Section: F I G U R E 2 Algorithm For the Initial Management And Subsementioning
confidence: 99%